2020
DOI: 10.1186/s13229-020-00371-0
|View full text |Cite
|
Sign up to set email alerts
|

Face individual identity recognition: a potential endophenotype in autism

Abstract: Background Face individual identity recognition skill is heritable and independent of intellectual ability. Difficulties in face individual identity recognition are present in autistic individuals and their family members and are possibly linked to oxytocin polymorphisms in families with an autistic child. While it is reported that developmental prosopagnosia (i.e., impaired face identity recognition) occurs in 2–3% of the general population, no prosopagnosia prevalence estimate is available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 153 publications
(210 reference statements)
5
34
1
1
Order By: Relevance
“…Autistic patients generally have obstacles in face naming, recognition, coding and other tasks from previous studies. It may be due to the formation of their unique eye movement gaze pattern, or because of the same neural mechanism behind both [18][19][20]. Based on the theoretical hypothesis, we verified the correlation between the PI-20 questionnaire and the AQ questionnaire.…”
Section: Discussionmentioning
confidence: 63%
“…Autistic patients generally have obstacles in face naming, recognition, coding and other tasks from previous studies. It may be due to the formation of their unique eye movement gaze pattern, or because of the same neural mechanism behind both [18][19][20]. Based on the theoretical hypothesis, we verified the correlation between the PI-20 questionnaire and the AQ questionnaire.…”
Section: Discussionmentioning
confidence: 63%
“…Face memory impairment, being associated with social and cognition development, has been a candidate neurocognitive endophenotype of autism spectrum disorder (ASD) [1][2][3][4]. For example, better face memory performance of children with ASD could predict their lesser independent play and more cooperative interaction with peers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported such associations between broader autism traits and facial memory (Brewer et al, 2019;Davies et al, 2017;Rhodes et al, 2013;Sasson et al, 2013;Lewis et al, 2018). Furthermore, recent evidence suggests that impaired face identity recognition is a potential endophenotype in autism i.e., it could be a co-occurring condition with prosopagnosia (Minio-Paluello et al, 2020).…”
Section: Correlations Between Cognitive and Behavioural Attributesmentioning
confidence: 98%
“…Individuals with autism (see 3.2.4) tend to exhibit face processing difficulties; however, these difficulties are reported based on their inability to possess sustained attention throughout life, and thus exhibiting difficulties in face processing. Evidence exploring the relationship between DP and autism have suggested that these two groups that predominantly exhibit difficulties in face processing and social dysfunction respectively, raises the possibility that these conditions co-occur in several cases (Minio-Paluello et al, 2020;Schultz, 2005). As such, it has been suggested that DP should be viewed as a disorder with face recognition difficulties independent of socio-emotional difficulties such as autism (e.g., Bate & Tree, 2017;Duchaine et al, 2009).…”
Section: What Is Developmental Prosopagnosia?mentioning
confidence: 99%
See 1 more Smart Citation